TRPC channels are not required for graded persistent activity in entorhinal cortex neurons - Egorov, Alexei V. (2019)
Adaptive behavior requires the transient storage of information beyond the physical presence of external stimuli. This short-lasting form of memory involves sustained (“persistent”) neuronal firing which may be generated by cell-autonomous biophysical properties of neurons or/and neural circuit dynamics. A number of studies from brain slices reports intrinsically generated persistent firing in cortical excitatory neurons following suprathreshold depolarization by intracellular current injection. In layer V (LV) neurons of the medial entorhinal cortex (mEC) persistent firing depends on the activation of cholinergic muscarinic receptors and is mediated by a calcium-activated nonselective cation current (ICAN). The molecular identity of this conductance remains, however, unknown. Recently, it has been suggested that the underlying ion channels belong to the canonical transient receptor potential (TRPC) channel family and include heterotetramers of TRPC1/5, TRPC1/4, and/or TRPC1/4/5 channels. While this suggestion was based on pharmacological experiments and on effects of TRP-interacting peptides, an unambiguous proof based on TRPC channel-depleted animals is pending. Here, we used two different lines of TRPC channel knockout mice, either lacking TRPC1-, TRPC4-, and TRPC5-containing channels or lacking all seven members of the TRPC family. We report unchanged persistent activity in mEC LV neurons in these animals, ruling out that muscarinic-dependent persistent activity depends on TRPC channels.